Kajian Terapan Konsep Crime Prevention Through Environmental Design (CPTED) pada Interior Rumah Tinggal Tipe Semi-Detached di Sidoarjo - Amy Kezia Santoso; Sherly de Yong; Purnama Esa Dora Tedjokoesomo (Intra, 2018)
Residential house is very essential for human being because it is a place for human to settle and have activities so that security must be adequate so human activity is not disturbed by existence of crime. The increasing number of criminal acts will affect the risk of crime in home so should be prevented. One way to prevent criminal action is using the concept of CPTED (Crime Prevention Through Environmental Design). This research is a qualitative research with case study approach. The case study object is a semi-detached type of residence in Sidoarjo. Stages of this research method is the collection of literature and field data, risk level vulnerability analysis of threats of criminal action and application of the concept of CPTED, proposing solutions, and conclusions. The research undertaken resulted in the identification of risk and vulnerability level of threats of criminal action on case study object and application of CPTED concept to object as well as proposed solution of CPTED concept application.